Building a team culture for Adaptive Management in MSD: 5 Strategies MEL Managers Say Work - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (MSD in MEL Brief, 2023)
Keywords: Bolder Meghan; Gover Dun; Henao Lina; Nasution Zulka; Okutu David

Systems-aware social accountability: Harnessing Practitioner Insights for More Responsive Governance - Guerzovich, Florencia (Pact, 2023)
The framework’s four principles, described below, are not exclusive to social accountability interventions; for example, Pact has published tools on how to use political economy analysis or integrate adaptive management principles into programming. Rather, the principles highlight how – by including the right combination of mindsets, management approaches, analytic approaches and tools – practitioners can develop and apply a deep understanding of a system to improve relationships within it, in support of greater accountability and improved service delivery. - Use a Holistic Lens - Recognize that there is always a system; understand and engage with it​: Developing a strong understanding of the system in which a project works and effectively integrating this knowledge into implementation increases the chances that local actors will sustain the interventions. - Right Fit the Approach​ - Equipped with a holistic understanding of the context, teams identify where they have a comparative advantage in a specific system. In other words, they identify where their resources, expertise and partners have the greatest potential for impact, then set realistic targets that they revise periodically. -Orchestrate Across The System -​ Practitioners take a networked, rather than a top-down, approach to capitalize on their convening power and maximize opportunity to facilitate the most-promising alignments across and within their projects, portfolios and systems. Orchestrators use their individual power, relationships and insight into the local system to enable, not impose, promising interactions and mitigate the risks of damaging ones. - Manage Adaptively - Monitor, evaluate and reflect on emerging patterns of data, evidence and learning to inform decision-making within and, equally importantly, across project cycles. Where possible, practitioners should consider how to use short-term projects to play a long-term game by linking new projects to the lessons and results of their predecessors and ensuring that they are responsive to the evolving context, particularly opportunities, limits and risks.

Enhancing partner and system-level learning: 8 Tips from MEL Managers - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (MSD in MEL Brief, 2023)
Effective learning is a key driver of market systems change, with the potential to enhance system competitiveness, resilience, and inclusiveness. Shifting the Locus of Learning: Catalyzing Private Sector Learning to Drive Systemic Change recently outlined a rationale for enhancing the scale and quality of learning in a system and identifying 10 strategies programs can contextualize to catalyze learning. These strategies are also backed with robust examples from 13 programs doing this work across 11 countries. To deepen insights on what MSD Monitoring, Evaluation and Learning (MEL) Managers have experienced in putting several of those strategies into practice, the Feed the Future Market Systems and Partnerships (MSP) Activity convened a series of peer discussions as part of a larger initiative (see Figure 1). This brief shares the collective learning and experience on this topic of three senior MEL Managers who were interested in and had experience with this topic. The group represented full-time, program-based MEL Leads working on MSD programs funded by USAID and DFAT, based in Fiji, Albania, and Kosovo working for Adam Smith International, SwissContact, and DT Global, respectively. From those discussions, this paper synthesizes eight tips from MEL Managers for practically enhancing partner and system-level learning: 1. Identify the right decision-maker(s) at potential partners. 2. Use a co-creation process to identify learning opportunities. 3. Use diagnostics and assessments to strengthen partner and system capacity for actionable learning. 4. Use a phased capacity strengthening process tied to behavior change. 5. Measure partners’ continued investment in and use of learning—not the continuation of specific learning activities. 6. Work with sector-level institutions for scale but be aware of risks. 7. Leverage informal communities of practice to share learning. 8. Use the right terminology to talk about partner and system-focused learning.

Practicing what we preach — our experience rethinking M&E in complex settings - Bina, Andrea; Vester, Søren (UNDP Strategic Innovation, 2023)
The UNDP has been exploring new approaches to M&E to better understand and address complex systems challenges. Traditional linear project-based planning and evaluation methods are insufficient for dealing with the unpredictable nature of such systems. The UNDP’s new Strategic Plan calls for a shift in M&E practices to align with the complexity of today’s global challenges. Key points from the blog post include: Learning and Adapting: There’s a need for continuous learning and adaptation in M&E practices to effectively address complex problems like transitioning to a circular economy. Longer Time Horizons: Substantive change takes time, and it’s often unclear what the results will look like, making it difficult to track progress. Aggregate Impact: Evaluating interconnected interventions as a portfolio is crucial because they cannot be assessed in isolation. Contribution vs. Attribution: Focusing on the contribution to broader change processes is more important than attributing specific outcomes to individual actions. The UNDP has initiated the M&E Sandbox to experiment with and learn from innovative M&E practices. This collaborative space has attracted participants from over 180 organizations, highlighting a shared interest in evolving M&E to better understand change in contexts of uncertainty. A partnership with the Bill and Melinda Gates Foundation has also been formed to focus on M&E in food systems. The blog post emphasizes the importance of embracing uncertainty, experimenting, and collaborating to contribute to positive change in complex settings1.

How to Build Movements with Cyclical Patterns in Mind - Non Profit News | Nonprofit Quarterly - Algoso, Dave; Guerzovich, Florencia; Gattoni, Soledad (Nonprofit Quarterly, 2023)
The world changes too much for anyone who is invested in social change work to imagine that this work is linear and predictable. Opportunities come and go, whether caused by a pandemic or political shifts. This much most social movement leaders and activists intuitively understand. But what can be done with this realization? How might movement groups better prepare for moments of opportunity? We want to explore how we can create the changes we want to see by responding to the changes that are outside our control.